Caracterización estructural y morfológica de nano partículas de (LaF3)0.75Er0.025Yb0.225 y (LaF3)0.75Er0.015Yb0.235 preparadas por coprecipitación química para el estudio de sus propiedades luminiscentes anti Stokes - García, Moises (2023)
Nanoparticles of (LaF3)0.75Er0.025Yb0.225 and (LaF3)0.75Er0.015Yb0.235  were synthesized using the chemical coprecipitation method and subjected to thermal treatment of 200 °C, 400 °C and 600 °C respectively for 2 hours. The structure of the samples was analyzed through the X-ray diffraction (XRD) technique and RIETVELD modeling by fundamental parameters using the TOPAS software. The size of the crystallites was found to be at nanometric level (between 119 nm and 140.7 nm) and the increment in size of the crystallites was verified as the temperature of the heat treatment was increased. It was possible to verify the change from hexagonal to rhombohedral structure for the samples subjected to 600 °C and a significant increment in the crystallinity of the samples due to the effect of thermal treatment. The SEM-EDS images show the described effects and provide a way to corroborate the growth of the particles (between 538 nm and 778 nm), as well as to obtain the elemental composition of the samples. Finally, the Raman spectrum show a low phonon energy of the samples (between  and), thus ensuring that the loss of the anti-Stokes emission properties of the excited states of the lanthanide ions in the samples due to the cooling effect is minimal.